Foreign ownership and firm performance: evidence from Malaysia - Mohd Abdullah Jusoh, (Fakulti Ekonomi dan Pengurusan, 2015)
It is a known fact that foreign multinational firms hold significant ownership in firms listed on Bursa Malaysia. These foreign owners do not only provide capital, but also managerial expertise and exceptional monitoring mechanism on managers. Therefore, it can be expected that foreign ownership improves firm performance and efficiency. However, the extent to which their participation in ownership could improve firm performance particularly in emerging countries such as Malaysia has to be empirically tested. This study investigates the relationship between foreign ownership and firm performance of public listed firms in Malaysia. Three years panel data of 730 Malaysian public listed firms were examined. The results show that foreign ownership has positive and significant relationship with ROA and Tobin’s Q. Therefore, the involvement of foreign investors in monitoring and controlling activities reduces agency conflict in the emerging economy. This is the first study that utilizes the extended agency theory to explain foreign ownership and performance in a developing country.